Improved mechanical and thermomechanical properties of alumina substrate via iron doping - Made, Riko I. (2013)
We present a method to improve the overall properties of sintered alumina substrate via iron doping that has a higher fracture toughness, lower thermal conductivity, lower thermal expansion coefficient and comparable dielectric constant to pure alumina. Such properties are beneficial for harsh environment electronic packages. X-Ray and electron probe micros analysis concluded that toughening are likely contributed by multiple phases strengthening and ruled out crack bridging or grain boundary strengthening.